Dose‐effect relationship between brisk walking and blood pressure in Chinese occupational population with sedentary lifestyles - Yingxiang YU; Cuiqing CHANG; Yifan WU; Chengcheng GUO; Lan XIE (The Journal of Clinical Hypertension, 2021)
Abstract The purpose of this study was to explore the effects of brisk walking on blood pressure (BP) in Chinese Han occupational populations to identify the appropriate volume of exercise needed for BP management. Eight‐hundred and two office staff with sedentary lifestyles were recruited to receive a prescription pedometer‐assisted brisk walking intervention for 3 months. To evaluate exercise intervention efficiency using statistical methods, the effective steps was divided as follows: 4000‐ < 8000 (Level 1), 8000‐ < 10 000 (Level 2), 10 000–12 000 (Level 3), and > 12 000 (Level 4) steps/day. The data of 688 participants who completed the study were analyzed. After intervention, Systolic BP (SBP) and Diastolic BP (DBP) at Levels 1–3 were significantly decreased (p < .05). For participants with hypertension at baseline, all four levels demonstrated a significantly reduced SBP and DBP. In addition, there was a significant dose‐effect relationship between the effective steps and the SBP. Compared with the maximum effective steps level (Level 4), the average change of SBP between level 1–3 and level 4 were statistically significant, with ‐3.24 mm Hg (95%CI: ‐5.74 to ‐0.74, p = .011), ‐2.58 mm Hg (95%CI: ‐4.73 to ‐0.43, p = .019), and ‐2.19 mm Hg (95%CI: ‐4.20 to ‐0.18, p = .033), respectively. For the hypertensive cohort, only the difference between Level 1 and 4 was statistically significant (Level 1 vs. Level 4: difference in means = ‐6.22 mm Hg, 95%CI: ‐12.68 to ‐0.24, p = .036). No significant dose‐effect relationship of DBP was observed. Our findings showed brisk walking can effectively control BP in Chinese populations and a significant dose‐effect relationship was found between exercise and SBP.